Prolific fruit output by the invasive tree Bellucia pentamera Naudin (Melastomataceae) is enhanced by selective logging disturbance. (26th March 2018) - Dillis, Christopher; Marshall, Andrew J.; Webb, Campbell O.; Grote, Mark N.
Abstract: Selective logging in tropical rain forests may promote population growth of invasive plants. The ability of invaders to respond, specifically in reproductive traits, to increase in resource abundance may allow them to increase their presence in the seed rain of recipient communities. The invasive pioneer tree Bellucia pentamera (Melastomataceae) is currently spreading within Gunung Palung National Park in West Kalimantan, Indonesia. The park has also experienced periods of illegal, small‐scale, selective logging that seem to have facilitated population growth and spread of this invader. We first used fruiting frequency as a proxy for fruit output to make comparisons between B. pentamera and the native tree community of over 200 genera. We then constructed two Generalized Linear Autoregressive Moving Average (GLARMA) models using 13 months of phenology data to predict both fruiting frequency and crop size of B. pentamera under selective logging versus natural treefall disturbance regimes. Bellucia pentamera fruited at considerably higher frequency than all 200 native genera considered. This invader also responded positively to selective logging with both odds of being in fruit and crop sizes at least doubling in logged plots. Prolific seed output of B. pentamera is especially problematic within the lottery competition of tropical rain forest gap tree communities, in which prominence in the seed rain is particularly important. Furthermore, the reproductive response of B. pentamera to selective logging suggests that this harvesting practice may have a considerable role in facilitating this invasion in Southeast Asia.